Análise de tecnologias de escanerização para medição de rugosidade de superfícies de madeiras - Cecchi, Leandro de Campos [UNESP] (2012)
The surface finish of the wood is an important parameter in respect the application of varnishes, adhesives and their industrial application. With the continuous expansion of the furniture market and quality requirements getting higher, the surface appearance and finishing is important and is linked to roughness of wood. The rugosimeter is the apparatus used for the benchmarking of surface irregularities, but it is designed for calibration of smoother surfaces as metal and polymers, and no organic materials like wood, it has vessels, lumens, flaws and cracks, which have a large amplitude on the scale of measurement. Seeking a solution to replace the rugosimeter and thus have better data on the surface was analyzed usability of 3D scanners that exist on the market. Based on manufacturer data and the requirements to make the measurement of surface roughness of the wood, it was possible to conclude that some of the scanners available in the market could be used for this purpose, providing information with greater reliability